Analisis Pengaruh Daya Mesin Dan Campuran Bahan Bakar Oli Bekas Dan Dexlite Terhadap Emisi Gas Buang CO2 Mesin Diesel Dongfeng Model R175 - Karina Yolanda; Aryo Sasmita; Yohannes Yohannes (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
Used oil is a potential alternative fuel and can reduce the waste of used oil. Used oil utilization has been carried out at The Production Technology Laboratory, Department of Mechanical Engineering, Riau University on modified diesel engines. The problem is that the resulting emissions still exceed the quality standard at a power load of 2000 W. In the present work, CO2 emission produced by Dongfeng R175 diesel engine with the mixed used oil and dexlite as alternative fuels was investigated. A total of three fuel samples, such as D10 (10% dexlite), D20 (20% dexlite), D30 (30% dexlite) respectively are used. CO2 emissions were analyzed with varied power loads, starting at idle, 1000 W, and 2000 W. The result was analyzed using a Microsoft Excel application with graphical output of the emission levels. The results showed that the best mixture was D10 where the highest loading power of 2000 W produced CO2 emission of 2,5%. While the highest CO2 emission produced by the D30 mixture at a power load of 2000 W of 6,6%.Keywords : Diesel Engine, Used Oil, Dexlite, Exhaust Emissions, CO2.